Abnormal Sexual Behavior During Sleep in an Adolescent: Sexsomnia and Defecation - Kapan, Oya Güleşen; Aydilek, Zeynep Ihtiyar; Kapan, Mustafa; Baştemur, Mehmet; Koç, Güray; Bodur, Şahin; Yetkin, Sinan; Cöngöloğlu, Mehmet Ayhan (Sleep Science, 2025)
Sexsomnia is characterized by sexual behaviors ranging from masturbation, sexual sounds, and verbalizations, to touching and full sexual intercourse during NREM sleep, with subsequent amnesia. Autonomic activation occurs with sexual arousal. Sexsomnia has been described mostly in adult males and is still an underrecognized condition. Treatment is often effective but without current consensus.In a case now reported of an adolescent male with sexsomnia, which is rarely reported in the literature, a novel feature that is now first reported is defecation accompanying sexsomnia as a co-occurring autonomic disturbance during sleep.
Keywords: adolescent; defecation; parasomnias; sexual behavior; sexsomnia